2011
DOI: 10.3390/ijms12053340
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene Enhances Antioxidant Enzyme Activities and Immunity Function in N-Methyl-N′-nitro-N-nitrosoguanidine–Induced Gastric Cancer Rats

Abstract: To investigate anticancer effect of lycopene, we examined the effects of lycopene on the oxidative injury and immunity activities of N-methyl-N′-nitro-N-nitrosoguanidine (MNNG)-induced gastric cancer rats. The animals were divided into five groups. Group I served as the normal control and was given corn oil orally for 20 weeks. Group II were induced with MNNG 200 mg/kg body weight by oral gavage at days 0 and 14, and saturated NaCl (1 mL per rats) was given once every three days for four weeks until the end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 49 publications
2
39
0
2
Order By: Relevance
“…Both the ethanolic extracts and in vitro digested samples of tomato (fruit and paste) showed potential of inhibiting lipid oxidation. The result correlate with the work of Luo and Wu (2011), where it was reported that lycopene treatment in rats, with induced gastric cancer significantly ameliorated an increased MDA level at the end of the experiment. Since flavonoid represent the major component of the total phenolic content in tomato (Toor & Savage, 2005), hence, the flavonoids, lycopene and other phenolic compounds present in tomato fruit and paste may be responsible for their ability to inhibit lipid peroxidation.…”
Section: Discussionsupporting
confidence: 90%
“…Both the ethanolic extracts and in vitro digested samples of tomato (fruit and paste) showed potential of inhibiting lipid oxidation. The result correlate with the work of Luo and Wu (2011), where it was reported that lycopene treatment in rats, with induced gastric cancer significantly ameliorated an increased MDA level at the end of the experiment. Since flavonoid represent the major component of the total phenolic content in tomato (Toor & Savage, 2005), hence, the flavonoids, lycopene and other phenolic compounds present in tomato fruit and paste may be responsible for their ability to inhibit lipid peroxidation.…”
Section: Discussionsupporting
confidence: 90%
“…This stimulation of lycopene on IgG production has been observed in other studies, like that carried out by Luo and Wu (2011), showing that lycopene can increase blood levels of IgA, IgG and IgM, improving the immunity of rats with cancer. Similarly, Neyestani et al (2007) observed that dietary supplementation of lycopene stimulates the formation of specific antibodies, mainly IgG isotype, reporting that lycopene is not only a common immune enhancer, because it provides an specific immune stimulation.…”
Section: Discussionsupporting
confidence: 50%
“…Suppression of COX-2 is another lycopene mediated effect. Similarly, in gastric carcinomas, lycopene up-regulates anti-oxidants and thereby exerts anti-neoplastic effects [4]. Lycopene also acts on hepatic tissue and mitigates the risk of developing hepato-cellular carcinoma, especially in the presence of background Hepatitis C infection [5].…”
mentioning
confidence: 99%